MENINGKATKAN KESADARAN AKAN ARTI PENTING ADMINISTRASI KEPENDUDUKAN MASYARAKAT LERENG MERAPI DESA CLUNTANG - SETYO LARAS; WISNU SANJAYA (KRIDA CENDEKIA, 2022)
Over the past two years, the virus pandemic has changed the pattern of people’s lives in various fields, including the economy and business, social, politics, education and technology. In the midst of the current pandemic, small, medium and large business actors must think hard in running their business. Since the issuance of the Village Law in 2014 (Law No.6), the government’s commitment to encouraging fiscal decentralization through the realization of village funds has continued to this day. The impact of this policy has been felt by many people, starting from the improved facilities and infrastructure of roads, bridges, irrigation canals, building village markets, dams, drainage and others. Thus, the challenge of poverty is still quite high in the midst of massive development in rural areas, the biggest challenge at this time is the economic crisis caused by the Covid-19 pandemic. The agricultural economic sectors in the rural environment during this crisis era were able to survive as indicated by the village market which was still running even though the prices of agricultural products were unstable. Village markets are places where producers, traders, and buyers in an agrarian society gather for the purpose of not only economic exchange but also social and cultural interaction. Some come as suppliers, retailers, and buyers of goods and services to fulfill their daily needs.